2018
DOI: 10.1149/2.0151806jes
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Analysis of Ionomer Loss in Catalytic Layers after Operation

Abstract: The function of catalytic layers in fuel cells and electrolyzers depends on the properties of the ionically conductive phase, which are most commonly perfluorinated ionomers based on Nafion and Aquivion. An analysis by atomic force microscopy reveals that the ultrathin ionomer films around Pt/C agglomerates have a thickness distribution ranging from 3.5 nm to 20 nm. Their conductivity and gas permeation properties determine the fuel cell performance to a large extend. For electrodes in Aquivion-based membranee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 79 publications
(121 reference statements)
3
30
0
Order By: Relevance
“…The above stated observations agree with our hypothesis of the ionomer "displacement," as one would except that this would be more prominent with a higher ionomer content in the CL. The ionomer displacement and redistribution, as well as loss of total ionomer fraction in the CL with operation time, were also observed by Morawietz et al 55 They reported that the ionomer displacement and redistribution resulted in a growth of bigger ionomer agglomerates after prolonged operation. Similar in our case, after operation, we observe the increase in amount and size of the ionomer fibers that are present in the CL/GDL interface.…”
Section: ) Which Ensures Comparability Between the Different Measurements (Refer To Table I For Details Of Each Mea)supporting
confidence: 64%
See 1 more Smart Citation
“…The above stated observations agree with our hypothesis of the ionomer "displacement," as one would except that this would be more prominent with a higher ionomer content in the CL. The ionomer displacement and redistribution, as well as loss of total ionomer fraction in the CL with operation time, were also observed by Morawietz et al 55 They reported that the ionomer displacement and redistribution resulted in a growth of bigger ionomer agglomerates after prolonged operation. Similar in our case, after operation, we observe the increase in amount and size of the ionomer fibers that are present in the CL/GDL interface.…”
Section: ) Which Ensures Comparability Between the Different Measurements (Refer To Table I For Details Of Each Mea)supporting
confidence: 64%
“…Furthermore, during the recovery step (> 120% RH), the presence of liquid water in the CL likely facilitates ionomer solving while creating micelles. 55 It is widely known that short side chain low EW ionomer have the propensity for dissolution and flow, compared to the high EW ionomers, which has been rationalized by the comparable higher ionomer water uptake. 58 Thus, the ionomer variant in the present study (725 EW), together with the ink composition and catalyst layer drying protocol used in this work, is prone to such ionomer flows and would irreversibly alter the ionomer distribution in the CL.…”
Section: ) Which Ensures Comparability Between the Different Measurements (Refer To Table I For Details Of Each Mea)mentioning
confidence: 99%
“…The material-sensitive and conductive atomic force microscopy (AFM) was used to show the ionomer distribution in CL. [13][14][15][16][17][18][19][20][21] The adhesion force image overlaid topography was used to distinguish the ionomer and the aggregated Pt/C. The ionically conductive regions, which implied the ionomer region in CL, could be recognized by their low adhesion signal.…”
Section: Introductionmentioning
confidence: 99%
“…Cullen 23 showed the ionomer coating lm thickness is about 7 nm using AFM technology. Hiesgen's group [15][16][17][18][19][20][21] had done a series of works on ionomer distribution in the CL by AFM. The AFM tip of nominal radius of less than 1 nm was used and an image pixel size was less than 1 nm (<0.36 nm) for high-resolution image.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation